The role of African Union in addressing maritime piracy in Eastern Africa. - Waweru, John Migui (My University, 2014)
Unable to copy abstract
Thesis (M.M. (Security))--University of the Witwatersrand, Faculty of Commerce, Law and Management, Graduate School of Public and Development Management, 2014.